(3QSGdI aj GdMceI GdeSJhQIs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3gPg QSGdI YedgG GdTjN GdMcje CHh Ydi Hf YHO Gddg Hf SjfG ai GdMceI GdeSJhQI s
(3BNQgG (B:s
(3heKGd GdcdS GdCQV hGdCHjV jJe ai KdGKI JeJ GdcJGH s
(3GdfSNI HgG MhGTs
(3GfXQ WHbGJ GdCWHGA L(B2 (3U(B2s
(3hLggG Edi GdTjN CHj GdMSf Sgd Hf eMeO GdSgdi s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdcjejGA h GdWHjYjGJs